2017
DOI: 10.1016/j.prro.2017.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Radiation oncology residency selection: A postgraduate evaluation of factor importance and survey of variables associated with job securement

Abstract: Background Medical students often choose to pursue a career in Radiation Oncology with limited meaningful exposure to the field. We previously identified factors which were most influential to an applicant’s rank list order. Here we sought to assess if residency graduates had differing views regarding those factors. We also polled recent graduates’ attitudes of the current job market. Material and Methods An anonymous, internet-based survey was developed and distributed to graduates of radiation oncology res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…This category was followed by curriculum design research (50, 34.2%); and reviews (8, 5.5%). Other research topics with more than ten publications between 2008 and 2017 included: training (25, 17.1%), contouring (20, 13.7%), career (17, 11.6%), technology (16,11.0%), resident well-being (15, 10.3%), multidisciplinary training (14, 9.6%), research (13,8.9%), and professionalism (12, 8.2%). The numbers of publications inside and outside the United States are also presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This category was followed by curriculum design research (50, 34.2%); and reviews (8, 5.5%). Other research topics with more than ten publications between 2008 and 2017 included: training (25, 17.1%), contouring (20, 13.7%), career (17, 11.6%), technology (16,11.0%), resident well-being (15, 10.3%), multidisciplinary training (14, 9.6%), research (13,8.9%), and professionalism (12, 8.2%). The numbers of publications inside and outside the United States are also presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Presently, there is an excess of radiation oncologists in the United States, but the number of residency slots has continued to expand [15]. Meanwhile, trainees gave more value to future job procurement because of the perception of a tightening job market [16]. In summary, the increasing interest in career-related topics originated from the motivation to understand where trainees came from and where they end up.…”
Section: Discussionmentioning
confidence: 99%
“…This regional bias is likely multifactorial involving a combination of personal factors and opportunities between residency programs with local hospitals/institutions. Notably, survey studies [4,12] have revealed that "geographic location" was a factor deemed very important by ROs in selecting their residency program and postgraduate employment.…”
Section: Discussionmentioning
confidence: 99%
“…The location of residency training and employment were categorized in four regions: Northeast (NE), South (S), Midwest (MW), and West (W) per the US Census Bureau [11]. Graduation year and location of first job were available for a subset of respondents who completed an internet-based survey as described in another study [4]. From the survey, two cohorts were identified, an early cohort which graduated from 2003-2006 and a late cohort which graduated from 2012-2015.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation